2014
DOI: 10.1155/2014/157216
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Apigenin on the Expression of Fas/FasL Apoptotic Pathway in Warm Liver Ischemia-Reperfusion Injury in Rats

Abstract: Background. The aim of this experimental study was to investigate the role of apigenin in liver apoptosis, in an experimental model of hepatic ischemia-reperfusion in rats. Materials and Methods. Forty-eight Wistar rats (apigenin and control groups), 14 to 16 weeks old and weighing 220 to 350 g, were used. They were all subjected to hepatic ischemia by occlusion of the hepatic artery and portal vein for 45 minutes and reperfusion was followed for 60, 120, and 240 minutes. Apigenin was administrated intraperito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
31
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 24 publications
1
31
0
3
Order By: Relevance
“…15 One of the typical features of liver diseases, such as I/R injury, is cell death, and apoptosis is the mainly pattern of it. 10 Bach1 plays an important role in targeting the Hmox1 (HO-1) gene; 17 by binding to the Maf recognition elements of the HO-1 gene, it inhibits transcription. Apoptosis repression represents a way to improve hepatocyte survival and minimize reperfusion injury.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…15 One of the typical features of liver diseases, such as I/R injury, is cell death, and apoptosis is the mainly pattern of it. 10 Bach1 plays an important role in targeting the Hmox1 (HO-1) gene; 17 by binding to the Maf recognition elements of the HO-1 gene, it inhibits transcription. Apoptosis repression represents a way to improve hepatocyte survival and minimize reperfusion injury.…”
Section: Discussionmentioning
confidence: 99%
“…6 The HO-1 enzyme can degrade the heme into carbon monoxide (CO), free iron, and biliverdin; 7 these products serve antiapoptotic and anti-inflammatory functions. 9 I/R injury is a continuous process; in the ischemic phase, the main injury is caused by oxygen-dependent cells 10 and in the reperfusion phase, the injury is enhanced by the accumulation of metabolic products, which leads to the generation of some toxic substances, such as free radicals, that eventually induce apoptosis. 9 I/R injury is a continuous process; in the ischemic phase, the main injury is caused by oxygen-dependent cells 10 and in the reperfusion phase, the injury is enhanced by the accumulation of metabolic products, which leads to the generation of some toxic substances, such as free radicals, that eventually induce apoptosis.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[30] Even more specifically in hepatic ischemia-reperfusion injury, Tsalkidou et al ., in 2014, have demonstrated that apigenin seems to affect the Fas/FasL mediated pathway of apoptosis, resulting in apoptosis inhibition. [31]…”
Section: Discussionmentioning
confidence: 99%